Pyrethroid Insecticides in Households from Urban Areas: An Association of the 3-PBA Metabolite and Hand Wipes - Jadsada Kunno; Parichat Ong-artborirak; Pongsaya Panicharoen; Mark Gregory Robson; Wattasit Siriwong (Ubiquity Press, 2020)
Background: Pyrethroid exposure in the household environment affects children directly via inhalation or dermal exposure. Hand wipes can effectively predict pyrethroid exposure to young children along with the children's activities. The main purpose of this study is to identify the relationship between 3-PBA metabolites, hand wipe sample concentrations and multiple exposure factors, within the population of households with young children in urban Bangkok, Thailand. Methods: Interviews were conducted with the parents of 80 children (aged 2-3 years). Urine was collected to analyze for 3-PBA metabolites and hand wipe samples were collected to analyze for cypermethrin. Both were analyzed by gas chromatography (GC/MS). Results: A Spearmen's correlation test of the increase of 3-PBA metabolites was significantly associated with an increase in hand wipe samples (cypermethrin) in children ('r's = 0.226-0.274, 'p'-value < 0.05). The binary logistic regression test presented an association between exposure factors with 3-PBA metabolite concentration. Gender presented a significant association with 3-PBA metabolites ('p'-value = 0.035, OR = 0.326, 95% CI 0.115-0.926), and frequency of bare feet inside the household presented a significant association with 3-PBA metabolites ('p'-value < 0.01, OR = 7.072, 95% CI 1.707-29.291). In addition, exposure factors were not significantly associated with wipe sample concentration (cypermethrin) but showed high risk of exposure to young children. Conclusions: Suggestions to reduce the risk from long-term pyrethroid insecticide exposure to children living in households include increased education, awareness, and management.